1997
DOI: 10.1152/jappl.1997.82.2.592
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2mediates increased pulmonary microvascular permeability after intestinal reperfusion

Abstract: This study examines the hypothesis that intestinal reperfusion (IR)-induced pulmonary thromboxane A2 (TxA2) release increases local microvascular permeability and induces pulmonary vasoconstriction. Sprague-Dawley rats underwent 120 min of intestinal ischemia and 60 min of IR. Sham-operated animals (Sham) served as controls. After IR or Sham, the pulmonary vessels were cannulated, and the lungs were perfused in vitro with Krebs buffer. Microvascular permeability was quantitated by determining the filtration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
3
21
0
1
Order By: Relevance
“…The concentration of U-46619 was chosen based on a dose-response curve relating increasing concentrations of U-46619 to increases in K f in this experimental system (data not shown). This concentration of U-46619 is associated with increases in K f similar to those seen with in vivo models of acute lung injury (29). Lastly, the increases in K f associated with U-46619 have been found to be completely inhibited by the thromboxane receptor antagonist SQ-29548 (2 µM; data not shown).…”
Section: Experimental Protocolsupporting
confidence: 54%
See 2 more Smart Citations
“…The concentration of U-46619 was chosen based on a dose-response curve relating increasing concentrations of U-46619 to increases in K f in this experimental system (data not shown). This concentration of U-46619 is associated with increases in K f similar to those seen with in vivo models of acute lung injury (29). Lastly, the increases in K f associated with U-46619 have been found to be completely inhibited by the thromboxane receptor antagonist SQ-29548 (2 µM; data not shown).…”
Section: Experimental Protocolsupporting
confidence: 54%
“…Pulmonary microvascular permeability was quantitated by determining K f as has been previously described by our laboratory (29) and that of other investigators (11,39). Briefly, 15 min after the addition of U-46619, the capillary pressure prior to elevating Ppv (Pc pre ) was measured using the double occlusion technique (1,28).…”
Section: Measurement Of Pulmonary Microvascular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both PGE 2 and PGI 2 enhance endothelial barrier and protect against ventilator-induced lung edema. 15 TXA 2 is reported to increase endothelial permeability and mediate intestinal reperfusion-induced pneumonia 16 and allergic nasal inflammation. 17 However, the mechanism by which PGD 2 modulates vascular permeability and inflammation remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the vasoactive effects of prostaglandins are likely involved in the pathogenesis of acute lung injury (Halushka et al, 1981;Wisner et al, 1988;Schuster and Haller, 1990;Stephenson et al, 1992;Schuster et al, 1993Schuster et al, , 1996Turnage et al, 1997;Gust et al, 1999b). In fact, acute lung injury is associated with increased tissue concentrations of the thromboxane metabolite TXB 2 (Gust et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%